Ectopic Kidney, a Challenging First Trimester Diagnosis—Case Report and Literature Review - Mircea-Octavian Poenaru; Fernanda-Ecaterina Augustin; Ionuț-Didel Vâlcea; Romina-Marina Sima; Mihaela Amza; Oana Denisa Bălălău; Liana Pleș (Life)
(1) Background: Crossed fused renal ectopia is a rare migration and fusion renal anomaly, more frequently affecting males, with an incidence of between 1:2000 and 1:7500 observed at autopsy. (2) Case presentation: This paper presents the case of a 34-year-old woman, IIIG IIIP, who presented to our clinic for a first-trimester screening evaluation. The risk calculation was performed using the Fetal Medicine Foundation’s first-trimester screening software, version 2.8.1. The screening indicated a low risk for aneuploidies, but the ultrasound scan revealed an empty right renal fossa in the standard coronal section. A more detailed axial examination raised the suspicion of crossed fused renal ectopia. No other anomalies were detected. The morphological scans conducted in the second and third trimesters confirmed and upheld the diagnosis initially established in the first trimester. The fetus did not develop any potential antepartum complications. The patient gave birth via caesarean section at 36 weeks to a live female infant, weighing 3000 g, with an APGAR score of 9 at 1 min. Postnatally, the first trimester diagnosis of the renal malformation was confirmed. (3) Conclusions: Crossed fused renal ectopia, probably the rarest renal migration anomaly, can be diagnosed as early as the first trimester of pregnancy.